Self-Detection of the LH Surge in Urine After GnRH Agonist Trigger in IVF—How to Minimize Failure to Retrieve Oocytes - Cozzolino, Mauro; Matey, Sonia; Alvarez, Abigail; Toribio, Mónica; López, Verónica; Perona, Marta; Henzenn, Elizabet; Piró, Manuel; Humaidan, Peter; Garcia-Velasco, Juan A. (Frontiers in Endocrinology, 2020)
Research question: Urine LH testing may be useful to confirm an LH surge after the GnRH agonist trigger prior to oocyte retrieval in IVF. Design: A prospective cohort study, including oocyte donors undergoing ovarian stimulation, treated with a GnRH agonist trigger for final oocyte maturation. Urine LH testing was performed at home, 12h after the GnRHa trigger. In the case of a negative result, serum LH and progesterone measurements were done that same day. Donors with no serum LH peak after trigger were re-scheduled using a dual trigger, with GnRHa and hCG. Results: 359 oocyte donors were included in the analysis. 356 donors had positive urine LH tests, followed by oocyte retrieval. In one case, the LH test was positive, however, no oocytes were retrieved (false positive rate 1/356). Three LH tests were negative in urine: in one of these three cases, LH was tested again in blood, confirming an LH rise, consistent with an optimal response to the GnRHa trigger; in the other two cases, serum LH was <15 mUI/mL, after which the oocyte retrieval was re-scheduled for 36h after an hCG trigger, resulting in the retrieval of 19 and 22 MII oocytes, respectively. Considering the cost analysis, it would be a significantly cost-saving strategy, as blood testing would have costed 14,840€ versus only 185.5€ in urine LH kits. Conclusions: Urinary testing of the LH surge after GnRHa trigger is easy, safe, reliable, and convenient. In addition, LH urine testing allows identifying donors and patients who could benefit from a rescue hCG trigger after an unsuccessful GnRHa trigger.